VD_FINDINFO Jug / 2012 / 136 vom 16. November 2011 - VD Tribunal cantonal (2011)
INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE, PRÉSOMPTION D'INNOCENCE, AVOCAT, HONORAIRES | 123 ch. 1 CP, 177 CP, 181 CP, 183 CP, 189 al. 1 CP, 190 al. 1 CP, 126 CPP (CH), 426 al. 4 CPP (CH)